Application of the 5S Kaizen Method to Increase Productivity in Kuningan Timur Village, Jakarta City - Rimadias, Santi (ASIAN PUBLISHER, 2023)
Increasing productivity is one of the main issues of concern in Indonesia. Thus it is necessary to make efforts to increase productivity sustainably in various sectors. The activity aims to increase the productivity of civil servants and local Kelurahan cadres through the application of the 5S Kaizen method. This activity was carried out at the Kuningan Timur Urban Village Office, Jakarta City from 2 to 4 May 2023 in the form of training. The training was attended by 20 participants consisting of civil servants and local village cadres. The method used in this activity is in the form of lectures, discussions, and direct practice. The results of the activity show an increase in knowledge and skills about 5S Kaizen, from good to very good at first. The direct practice of 5S Kaizen also gives very satisfying results. In the future, it is hoped that there will be a commitment to implementing 5S Kaizen so that productivity can continue to increase.